2019
DOI: 10.1186/s13019-019-1004-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adults undergoing transthoracic device closure of ventricular septal defect

Abstract: Objective: To evaluate the health-related quality of life (HRQoL) of adult patients who underwent transthoracic device closure of ventricular septal defect (VSD). Methods: During the perioperative and postoperative period, a standard scale involving eight dimensions was used to analyze the HRQoL of 85 adult patients who underwent thoracic device closure of VSD and 80 healthy adults located locally were randomly selected as the control group in our center. Results: A total of 80 patients' and 80 healthy adults'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…At present, most of the studies on the QoL of VSD have focused on children and adolescents [18,19]. In our previous study, we found that the short-term QoL of adult patients was improved after undergoing transthoracic device closure of VSDs [20]. In this study, the corresponding mid-term QoL of adult patients also showed an improvement trend, and such improvement was not transient.…”
Section: Discussionsupporting
confidence: 63%
“…At present, most of the studies on the QoL of VSD have focused on children and adolescents [18,19]. In our previous study, we found that the short-term QoL of adult patients was improved after undergoing transthoracic device closure of VSDs [20]. In this study, the corresponding mid-term QoL of adult patients also showed an improvement trend, and such improvement was not transient.…”
Section: Discussionsupporting
confidence: 63%
“…However, there has been no cross-sectional comparison between the two treatments, so research on the different effects of these two treatments on the postoperative HRQoL of adult patients is still needed. [18][19][20][21] In this study, we found that there was no significant difference in SF-36 scores between groups A and B except for the two dimensions of vitality and mental health. The reason might be that the patients subjectively felt that the transcatheter procedure had less impact on the body than the transthoracic procedure and thus had more positive feedback in the psychological domain.…”
Section: Discussionmentioning
confidence: 54%
“…The location and the surrounding structure of the VSD are essential factors in the procedure success. Many kinds of literature have shown that the transthoracic device closure of VSD not only virtually ensures the therapeutic effect, but also reduces the length of the incision, reduces the postoperative pain, and shortens the length of hospital stay [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous device closure has the advantage of no incision and fast recovery but has the disadvantage of Xray exposure. In recent years, our center has tried to treat the simple VSD using transthoracic device closure and has achieved good results [2][3][4]. In order to meet the needs of short anesthesia time and early tracheal extubation after transthoracic device closure of VSDs, fast-track anesthesia was adopted in our cardiac center.…”
Section: Introductionmentioning
confidence: 99%